SPRING: Scaling, Placement, and Routing of Heterogeneous Services with Flexible Structures - Dräxler, Sevil; Karl, Holger (5th IEEE International Conference on Network Softwarization (NetSoft) 2019)

Requirements Engineering in OTF-Computing - Bäumer, Frederik Simon; Geierhos, Michaela (encyclopedia.pub)
Keywords: OTF Computing; Natural Language Processing; Requirements Engineering

An Exact Branch-and-Price Algorithm for Scheduling Rescue Units during Disaster Response - Rauchecker, Gerhard; Schryen, Guido (European Journal of Operational Research)
In disaster operations management, a challenging task for rescue organizations occurs when they have to assign and schedule their rescue units to emerging incidents under time pressure in order to reduce the overall resulting harm. Of particular importance in practical scenarios is the need to consider collaboration of rescue units. This task has hardly been addressed in the literature. We contribute to both modeling and solving this problem by (1) conceptualizing the situation as a type of scheduling problem, (2) modeling it as a binary linear minimization problem, (3) suggesting a branch-and-price algorithm, which can serve as both an exact and heuristic solution procedure, and (4) conducting computational experiments - including a sensitivity analysis of the effects of exogenous model parameters on execution times and objective value improvements over a heuristic suggested in the literature - for different practical disaster scenarios. The results of our computational experiments show that most problem instances of practically feasible size can be solved to optimality within ten minutes. Furthermore, even when our algorithm is terminated once the first feasible solution has been found, this solution is in almost all cases competitive to the optimal solution and substantially better than the solution obtained by the best known algorithm from the literature. This performance of our branch-and-price algorithm enables rescue organizations to apply our procedure in practice, even when the time for decision making is limited to a few minutes. By addressing a very general type of scheduling problem, our approach applies to various scheduling situations.
Keywords: OR in disaster relief; disaster operations management; scheduling; branch-and-price

Digitalization of Work Systems—An Organizational Routines’ Perspective - Wolf, Verena; Bartelheimer, Christian; Beverungen, Daniel (Proceedings of the 52nd Hawaii International Conference on System Sciences (HICSS-52))

Pricing and issuance dependencies in SFP portfolios - Pelster, Matthias; Schertler, Andrea (Journal of Futures Markets)
We exploit a unique sample of structured financial products (SFPs) to analyze pricing and issuance dependencies among different types of such market‐linked investment vehicles. Our study provides evidence of cross‐pricing between products with complementary payoff profiles. Such dependencies may be explained by issuers’ efforts to generate order flow for products that supplement their current SFP risk exposure. Additionally, we observe issuance patterns in line with the argument that issuers exploit the complementarity payout profiles when bringing SFPs to market. Our study emphasizes cross‐pricing from a perspective not previously considered in the literature.
Keywords: cross‐pricing; discount certificate; hedging; issuance decisions; put warrants; structured financial products

Topic Modeling as a Strategy of Inquiry in Organizational Research: A Tutorial With an Application Example on Organizational Culture - Schmiedel, T.; Müller, Oliver; vom Brocke, J. (Organizational Research Methods)
Keywords: online reviews; organizational culture; structural topic model; topic modeling; tutorial

Supporting learning at work in an era of digitalization of work - Harteis, Christian (Work-based learning as a pathway to competence-based education)

Design of Review Systems – A Strategic Instrument to shape Online Reviewing Behavior and Economic Outcomes - Gutt, Dominik; Neumann, Jürgen; Zimmermann, Steffen; Kundisch, Dennis; Chen, J. (Journal of Strategic Information Systems)

Process Weakness Patterns for the Identification of Digitalization Potentials in Business Processes - Rittmeier, Florian; Engels, Gregor; Teetz, Alexander (Business Process Management Workshops)

Praxissemester und Professionalisierung - Überlegungen zur Gestaltung einer universitären Begleitkonzeption - Kremer, H.-Hugo (Berufsbildung zwischen Tradition und Moderne)

Als Wirtschaftsinformatiker die digitale Transformation in Organisationen gestalten - Kundisch, Dennis; Beverungen, Daniel

Combining Android Apps for Analysis Purposes - Zhang, Shikun

Modeling Crypto API usages in OpenSSL's EVP library - Selbach, Nils

Credence Goods Markets with Heterogeneous Experts - Heinzel, Joachim Maria Josef
In this paper, we analyze a credence goods model adjusted to the health care market with regulated prices and heterogeneous experts. Experts are physicians and are assumed to differ in their cost of treating a small problem. We investigate the effects of this heterogeneity on the physicians’ level of fraud and on the patients’ search for second opinions. We find that introducing a fraction of more efficient low-cost physicians always increases social welfare, but in some cases only because of the raised physicians’ surplus. When the low-cost physicians’ cost advantage is small, imposing a share of low-cost physicians does not change the equilibrium fraud level. When the cost advantage is large, however, different changes in the fraud level occur depending on the share of generated low-cost physicians, the search rate and the initial level of fraud.
Keywords: credence goods; treatment efficiency; heterogeneous experts; overcharging

Testing Machine Learning Algorithms for Balanced Data Usage - Sharma, Arnab; Wehrheim, Heike (IEEE International Conference on Software Testing, Verification and Validation (ICST))

MultiSkipGraph: A Self-stabilizing Overlay Network that Maintains Monotonic Searchability - Luo, Linghui; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 2019 IEEE 33rd International Parallel and Distributed Processing Symposium (IPDPS '19))
Self-stabilizing overlay networks have the advantage of being able to recover from illegal states and faults. However, the majority of these networks cannot give any guarantees on their functionality while the recovery process is going on. We are especially interested in searchability, i.e., the functionality that search messages for a specific node are answered successfully if a node exists in the network. In this paper we investigate overlay networks that ensure the maintenance of monotonic searchability while the self-stabilization is going on. More precisely, once a search message from node u to another node v is successfully delivered, all future search messages from u to v succeed as well. We extend the existing research by focusing on skip graphs and present a solution for two scenarios: (i) the goal topology is a super graph of the perfect skip graph and (ii) the goal topology is exactly the perfect skip graph.

Debiasing Vandalism Detection Models at Wikidata - Heindorf, Stefan; Scholten, Yan; Engels, Gregor; Potthast, Martin (WWW)

A Digital Twin-Based Multi-Modal UI Adaptation Framework for Assistance Systems in Industry 4.0 - Josifovska, Klementina; Yigitbas, Enes; Engels, Gregor (Proceedings of the 21st International Conference on Human-Computer Interaction (HCII 2019))

Transparent Acceleration for Heterogeneous Platforms with Compilation to OpenCL - Riebler, Heinrich; Vaz, Gavin Francis; Kenter, Tobias; Plessl, Christian (ACM Trans. Archit. Code Optim. (TACO))
Keywords: htrop

Vertrauensbildung und Reputationssysteme auf digitalen B2B-Märkten - Ein klassifizierender Überblick - Nutt, Florian